Impacts of Coarctation Coexisting with Other Cardiovascular Diseases on Hemodynamics Using Patient Specific Lumped Parameter and Lattice Boltzmann Modeling - Sadeghi, Reza (My University, 2021)
Effective diagnosis of COA hinges on quantifications of the global hemodynamics (heart function metrics and workload), and the local hemodynamics (3-dimensional flow dynamics in COA). In this study, we developed an image-based framework that can quantify local and global hemodynamics for COA diagnosis. The proposed framework uses lattice Boltzmann method and lumped-parameter modeling that only needs routine non-invasive clinical patient data. The computational framework was validated against clinical cardiac catheterization data and Doppler echocardiographic measurements. One of the complicating factors of COA is its common association with mixed valvular diseases (MVD), which include varying combinations of aortic and mitral valve pathologies. Treatment strategies for these patients are quite unclear and differ from patient to patient. In order to evaluate risk factors and create guidelines for intervention aimed at minimizing the progression of cardiovascular disease, the impact of COA and MVD on aortic fluid dynamics in patients with COA and MVD was investigated in this thesis. Our results show that interaction of MVD with COA fluid dynamics may amplify adverse hemodynamic effects especially downstream of COA and may contribute to speed up the progression of the disease. The results suggest that some more aggressive surgical approaches may be required as regularly chosen current surgical techniques may not be optimal for patients with both COA and MVD. The appropriate surgical technique for COA repair often remains unclear for adult patients. Extra-anatomical bypass grafting has been recommended in some of the COA cases. To effectively evaluate risk status and create guidelines for intervention, precise quantification of aortic fluid dynamics and hemodynamics is required. We used a patient-specific numerical framework to investigate the impact of bypass grafts on aortic fluid dynamics in patients with COA. This study can partially explain the complications associated in patients with COA who underwent bypass grafting.
Keywords: Coarctation of the aorta